Supporting Vulnerable Health Systems Improve Infection Prevention and Control to Fight the COVID-19 Pandemic - Bedoya, Guadalupe (World Bank, Washington, DC, 2020)
Protecting healthcare workers and patients is critical to reduce the spread of the disease. In this brief we highlight three urgent actions : Distribution of infection prevention and control (IPC) policies and guidelines to all health facilities; Manufacturing and distribution of IPC supplies to health facilities; and Mass media hand hygiene behavior change campaigns for health workers and the general population.